A Three‐Minute Synthesis and Purification of Ibuprofen: Pushing the Limits of Continuous‐Flow Processing1. Issue 3 (2nd December 2014) - Snead, David R.; Jamison, Timothy F.
Abstract In a total residence time of three minutes, ibuprofen was assembled from its elementary building blocks with an average yield of above 90 % for each step. A scale‐up of this five‐stage process (3 bond‐forming steps, one work‐up, and one in‐line liquid–liquid separation) provided ibuprofen at a rate of 8.09 g h−1 (equivalent to 70.8 kg y−1) using a system with an overall footprint of half the size of a standard laboratory fume hood. Aside from the high throughput, several other aspects of this synthesis expand the capabilities of continuous‐flow processing, including a Friedel–Crafts acylation run under neat conditions and promoted by AlCl3, an exothermic in‐line quench of high concentrations of precipitation‐prone AlCl3, liquid–liquid separations run at or above 200 psi to provide solvent‐free product, and the use of highly aggressive oxidants, such as iodine monochloride. The use of simple, inexpensive, and readily available reagents thus affords a practical synthesis of this important generic pharmaceutical.